Răspuns:
Explicație pas cu pas:
125 + { 14 × [ 40 + ( a + 240 ) : 4 ] - 34 } × 14 = 38 849
{ 14 × [ 40 + ( a + 240 ) : 4 ] - 34 } × 14 = 38 849 - 125
{ 14 × [ 40 + ( a + 240 ) : 4 ] - 34 } × 14 = 38 724
14 × [ 40 + ( a + 240 ) : 4 ] - 34 = 38 724 : 14
14 × [ 40 + ( a + 240 ) : 4 ] - 34 = 2 766
14 × [ 40 + ( a + 240 ) : 4 ] = 2 766 + 34
14 × [ 40 + ( a + 240 ) : 4 ] = 2 800
40 + ( a + 240 ) : 4 = 2 800 : 14
40 + ( a + 240 ) : 4 = 200
( a + 240 ) : 4 = 200 - 40
( a + 240 ) : 4 = 160
a + 240 = 160 × 4
a + 240 = 640
a = 640 - 240